2022
DOI: 10.1002/ana.26362
|View full text |Cite
|
Sign up to set email alerts
|

Human Metabotropic Glutamate Receptor 5 Antibodies Alter Receptor Levels and Behavior in Mice

Abstract: Ophelia syndrome or encephalitis with antibodies against the metabotropic glutamate receptor 5 (mGluR5) manifests with behavioral changes, memory deficits, and anxiety. To study the antibody pathogenicity, mice received continuous cerebroventricular infusion of patients' or controls' immunoglobulin G (IgG) for 14 days, followed by a 15‐day washout. The effects on hippocampal mGluR5 clusters were determined by confocal microscopy. Animals infused with patients' IgG, but not controls' IgG, showed memory impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…These results were similar to the previous findings (7). A recent study has revealed that mGluR5 antibodies can reduce the level of mGluR5 in the hippocampus, causing memory loss and anxiety in mice, which was in agreement with the clinical phenotype of anti-mGluR5 encephalitis (6). Other common neurologic symptoms include sleep disturbances, seizures, decreased level of consciousness, and movement disorders, which is align with previous studies (4, 7-9).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These results were similar to the previous findings (7). A recent study has revealed that mGluR5 antibodies can reduce the level of mGluR5 in the hippocampus, causing memory loss and anxiety in mice, which was in agreement with the clinical phenotype of anti-mGluR5 encephalitis (6). Other common neurologic symptoms include sleep disturbances, seizures, decreased level of consciousness, and movement disorders, which is align with previous studies (4, 7-9).…”
supporting
confidence: 92%
“…Autoimmune encephalitis with mGluR5 antibodies was first reported in two patients with limbic encephalitis and Hodgkin's lymphoma (Ophelia syndrome) in 2011 (4). A recent study in an animal model has confirmed the pathogenicity of mGluR5 antibodies, which causes a reduction of mGluR5 clusters in neurons (6). However, as far as we know, since 2011, only 15 autoimmune encephalitis patients with mGluR5 antibodies from 8 studies have been reported worldwide, including three case reports from China (4,(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The prevailing pathogenic hypothesis of post‐HSE anti‐NMDAR encephalitis suggests that viral infection damages neurons and exposes NMDAR antigens located on the neuronal surface, initiating a series of autoimmune responses (Dalmau & Graus, 2018). Given that mGluR5s are widespread in the brain, a reduced density of mGluR5 clusters on the neuronal surface was noticed in anti‐mGluR5 encephalitis (Maudes et al., 2022), we speculate that the mechanism of post‐HSE anti‐mGluR5 encephalitis is similar to anti‐NMDAR encephalitis.…”
Section: Discussionmentioning
confidence: 61%
“…However, nothing was known about the pathological mechanisms of the autoantibodies until 2018, when it was found that patient mGluR5 autoantibodies, mainly of the IgG1 subclass, decreased the amount of mGluR5 clusters on rat hippocampal neurons [ 86 ]. In 2019, it was further reported that the patient’s autoantibodies caused anxiety and progressive memory loss in mice [ 165 ]. The two publications have been authored by the same group and none of the pathological mechanisms have been validated by an independent research group.…”
Section: Autoantibodies With Extracellular Targetsmentioning
confidence: 99%